2016
DOI: 10.1007/s00704-016-1927-2
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal cycle of precipitation over Fujian Province during the pre-summer rainy season in southern China

Abstract: Precipitation diurnal cycle over Fujian in the presummer rainy season has been revealed based on the hourly rain gauge data during [2009][2010][2011][2012][2013]. The precipitation amount (PA) over northwestern Fujian and most southeast coasts shows relatively small diurnal variability. This is in contrast to large diurnal variations in the mountainous areas. Regional differences in precipitation diurnal cycles are obviously noted among the coastal, valley, hilly, and mountainous areas. The precipitation diurn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 49 publications
(68 reference statements)
0
11
0
Order By: Relevance
“…For all elevations, the diurnal variation of three parameters has one dominant peak. There is no apparent increase in the number of peaks with an increase in altitude, as observed in China (Zhang et al ., 2017). The most remarkable signal of topographic influence is the change of amplitude of PA and PF's diurnal variation (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For all elevations, the diurnal variation of three parameters has one dominant peak. There is no apparent increase in the number of peaks with an increase in altitude, as observed in China (Zhang et al ., 2017). The most remarkable signal of topographic influence is the change of amplitude of PA and PF's diurnal variation (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…Correlations of terrain height with PA, PF, and PI, are 0.10, 0.25, and 0.24, respectively, indicating a slight increase of the three parameters with increasing elevation. However, these correlations are not significant and much weaker than those found in other regions such as China (Zhang et al ., 2017; Li et al ., 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many recent studies have revealed that the diurnal variations of precipitation over eastern China are strongly influenced by the East Asia monsoon and topographic contrast. Over southeastern China, the spatial distributions of precipitation diurnal cycles in midsummer are primarily dependent on topography (Chen et al, 2010;Zhang et al, 2017;Wu et al, 2018). Over Shandong Province of eastern China, the precipitation over the inland areas strengthens in the afternoon due to the sea breeze, which may enhance the afternoon peak of precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…The precipitation diurnal peak in the afternoon appears earlier in the coastal northern plain than in the central northern plain (Zhuo et al, 2014). Over Fujian Province of southeastern China, the precipitation diurnal cycles are different among the coastal, valley, hilly, and mountainous areas during pre-summer (Zhang et al, 2017). The precipitation diurnal variation over Taiwan in the warm season is the result of local forcing involving solar thermal heating and island-scale land-sea breezes interacting with orography (Chen et al, 2012;Huang and Wang, 2014;Huang and Chang, 2018).…”
Section: Introductionmentioning
confidence: 99%